A Systematic Review: Chitosan/ Poly (vinyl alcohol) based Hydrogel composites for Drug Delivery Material - Annifah, Riri Uswatun; Kadarohman, Asep; Khoerunnisa, Fitri; Nurhayati, Mita; Hendrawan, Hendrawan; Anwar, Budiman (Jurnal Kartika Kimia, 2024)
This review article aims to systematically describe the synthesis methods, characterization, and performances of CS/PVA based hydrogel composites as drug delivery materials. The literature review was conducted through ScienceDirect and Google Scholar, where the article selection is based on Scopus index in the Q1 and Q2 categories within the past 5 years. The synthesis of CS/PVA hydrogel was performed using various methods, including crosslinking, freeze-thaw, and sol-gel. The synthesis methods of hydrogel composites included crosslinking, freeze-thaw, and sol-gel. Characterization of hydrogel composites was conducted using FTIR spectroscopy, SEM, and swelling ratio measurement. CS/PVA-based hydrogel composites as drug delivery materials have been successfully synthesized using crosslinker, freeze-thaw and sol-gel methods. FTIR spectra indicated that drug was successfully loaded into CS/PVA based hydrogel composite matrix, involving the hydrogen bonding as predominant mechanism of interaction between precursors and drug functionalities. The best swelling capacity was obtained in the CS/PVA/Tetracycline based hydrogel composites, up to 949%. The SEM images indicated the homogeneous morphological structure and surface of hydrogel composites. The CS/PVA/Tetracycline based hydrogel composites exhibited the largest cumulative drug release of 99.44%. The drugs loaded CS/PVA hydrogel composites are promising as a drug delivery material.